Using Google Meet in History Learning to Support Distance Learning in the Digital Age - Rendi Marta Agung; Muhammad Rijal Fadli (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The purpose of this article is to explain the effectiveness of using Google Meet in history learning as a support for distance learning (PJJ) in the digital era. The method used is a descriptive quantitative approach with experimental design. The sampling technique used purposive sampling with a sample of 32 students and 1 teacher. The technique of collecting data is through a questionnaire in the form of pre-test and post-test statements with a Likert scale of 5 to assess the usefulness of google meet. Data analysis used the paired sample t-test to determine whether or not there was an influence between the two variables assisted by the SPSS Version 26 program. The results showed that the use of google meet in history learning during the pandemic was declared effective so that the ongoing learning activities ran optimally, although there are many obstacles, can be overcome with coordination between the actors involved. The use of google meet can have implications for history learning which will be more meaningful during the pandemic because it is equipped with video conferencing so that it becomes a virtual class.